Media Consumption and Media Behavior of Contemporary Russian Youth as Constructs of Protest Identity - Tazitdinovich Mukhaev, Rashid (2021)
The relevance of the study topic is not only due to the very fact of the unauthorized gatherings in Russia on 24 and 31 January and 2 February, in which many young people, including minors, took part. The protests were inspired by the "Western mentors" of the Russian non-systemic opposition. It is equally important to understand the underlying reasons for the high involvement of young people in the protests in the context of the COVID-19 pandemic and the Western sanctions regime that has been running for seven years. The objective of the study is to analyze the causes, anatomy, technologies, and forms of protest representations of contemporary youth in Russia. The authors focus on the behavioral patterns of young people, the mechanism and content of which are now forming in the Internet space with the help of social networks. The means of recognizing social reality, markers of evaluation and its interpretation by the youth audience, and an algorithm for action are set by the Internet and social networks. Today, in many ways, Western digital giants determine the media consumption patterns, media behavior, and social practices of Russian youth. In this situation, it is important for the Russian state not to restrict access to the Internet but rather to shape a high political media culture among modern youth.